Neuroblastoma among children in Southern and Eastern European cancer registries: Variations in incidence and temporal trends compared to US. Issue 10 (29th December 2017) - Georgakis, Marios K.; Dessypris, Nick; Baka, Margarita; Moschovi, Maria; Papadakis, Vassilios; Polychronopoulou, Sophia; Kourti, Maria; Hatzipantelis, Emmanuel; Stiakaki, Eftichia; Dana, Helen; Bouka, Evdoxia; Antunes, Luis; et al.
Abstract : Neuroblastoma comprises the most common neoplasm during infancy (first year of life). Our study describes incidence of neuroblastoma in Southern–Eastern Europe (SEE), including – for the first time – the Nationwide Registry for Childhood Hematological Malignancies and Solid Tumors (NARECHEM‐ST)/Greece, compared to the US population, while controlling for human development index (HDI). Age‐adjusted incidence rates (AIR) were calculated for 1, 859 childhood (0–14 years) neuroblastoma cases, retrieved from 13 collaborating SEE registries (1990–2016), and were compared to those of SEER/US ( N = 3, 166; 1990–2012); temporal trends were assessed using Poisson regression and Joinpoint analyses. The overall AIR was significantly lower in SEE (10.1/million) compared to SEER (11.7 per million); the difference was maximum during infancy (43.7 vs . 53.3 per million, respectively), when approximately one‐third of cases were diagnosed. Incidence rates of neuroblastoma at ages <1 and 1–4 years were positively associated with HDI, whereas lower median age at diagnosis was correlated with higher overall AIR. Distribution of primary site and histology was similar in SEE and SEER. Neuroblastoma was slightly more common among males compared to females (male‐to‐female ratio: 1.1), mainly among SEE infants. Incidence trends decreased in infants in Slovenia, Cyprus and SEER and increased in Ukraine and Belarus. The lower incidence in SEE compared to SEER, especially in infants living in low HDI countries possibly indicates a lower level of overdiagnosis in SEE. Hence, increases in incidence rates in infancy noted in some subpopulations should be carefully monitored to avoid the unnecessary costs health impacts of tumors that could potentially spontaneously regress. Abstract : What's new? Neuroblastoma is an enigmatic tumor known to regress spontaneously in infants. Geographical differences in neuroblastoma incidence rates have been partially ascribed to overdiagnosis or underdiagnosis in high‐income or low‐income countries, respectively. Here, the authors compare incidence patterns in Southern‐Eastern Europe with the United States in a large study that unveils a possible over‐diagnosis in countries of advanced medical services, as suggested by the observed positive association of incidence rates with human development index. The results further stipulate the need for close monitoring of incidence and mortality to avoid unnecessary treatment while ensuring the best possible outcome for all diagnosed patients.